Industrial Chemistry - Benvenuto, Mark Anthony (De Gruyter Textbook, 2013)
Industrial Chemistry is a book that brings the subject matter of a chemistry curriculum to life. Comprehensibly written, it examines the major chemistry performed by industry and looks at how such chemical processes affect our lives. In addition, as each process is presented and examined, there is a significant discussion dedicated to the by-products, pollution, necessary waste generated, and attempts to make each process ecologically friendlier, or,'greener'. It bridges the divide between the basic chemistry that students learn in their undergraduate curriculum, and the broader chemical processes that are used in real life.